2021
DOI: 10.3390/pharmaceutics13050615
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable Protein Powder Prepared by Spray-Freeze-Drying Using Hydroxypropyl-β-Cyclodextrin as Excipient

Abstract: The prospect of inhaled biologics has garnered particular interest given the benefits of the pulmonary route of administration. Pertinent considerations in producing inhalable dry powders containing biological medicines relate to aerosol performance and protein stability. Spray-freeze-drying (SFD) has emerged as an established method to generate microparticles that can potentially be deposited in the lungs. Here, the SFD conditions and formulation composition were evaluated using bovine serum albumin (BSA) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To overcome the poor aqueous solubility of tamibarotene, TBA and ethanol were used as co-solvents in the feed solution for SFD and SD, respectively, with HPBCD used as excipient ( Jacob and Nair, 2018 , Lo et al, 2021 ). The sublimation of the frozen TBA crystals during freeze drying resulted in the formation of pores that could be seen in SFD powders.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the poor aqueous solubility of tamibarotene, TBA and ethanol were used as co-solvents in the feed solution for SFD and SD, respectively, with HPBCD used as excipient ( Jacob and Nair, 2018 , Lo et al, 2021 ). The sublimation of the frozen TBA crystals during freeze drying resulted in the formation of pores that could be seen in SFD powders.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrapure water was used to rinse and dissolve the powder deposited on all stages of the NGI. The collected samples were filtered through a 0.45-μm membrane filter and the concentration of HPBCD was quantified by an established high-performance liquid chromatography (HPLC) method as previously described [ 16 ]. Fifty microlitres of sample was injected into two conjoined Hi-Plex H guard columns (Agilent Technologies, Santa Clara, CA, USA) with ultrapure water as the mobile phase at 65 °C, running at a flow rate of 0.6 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Lo et al . [ 108 ] have reported that the spray freeze drying of bovine serum albumin (BSA) using hydroxypropyl-β-cyclodextrin (HPβCD) as the stabilizer resulted in spherical and porous particles and fine particle fractions in the range of 50–80% (using Breezhaler®) alongside MMADs in the range of 1–2.5 microns. The authors also concluded that among the process parameters investigated the atomization gas flow rate had the maximum effect on the aerosolization properties of the spray freeze–dried particles compared to solute and BSA concentration in the feed stock.…”
Section: Description Of Pfizer’s Mrna Covid-19 Vaccine Formulation Bn...mentioning
confidence: 99%
“…(2021) [ 107 ] Not applicable Spray-dried interleukin-8 using phosophate-buffered saline as the dissolution media Dry powder versions of interleukin were shown to be stable after 12 weeks of storage without any signs of protein unfolding, compromised binding affinity Lo et al . 2021 [ 108 ] Size 3 gelatin capsule (Capsugel®, Morristown, NJ, USA) was loaded into Breezhaler® (Novartis AG, Basel, Switzerland) Spray freeze–dried bovine serum albumin using hydroxypropyl beta-cyclodextrin as the protein stabilizer FPF in the range of 60 to 80% and MMAD in the range of 1–5 micron were reported for the tested formulations based on NGI studies Liang et al . (2018) [ 109 ] Breezhaler® (Novartis AG, Basel, Switzerland) Spray freeze–dried powders of DNA and siRNA FPF of 28% from NGI studies were reported along with intact structure of siRNA post spray drying Otake et al .…”
Section: Description Of Pfizer’s Mrna Covid-19 Vaccine Formulation Bn...mentioning
confidence: 99%